Factors Associated with Previable Delivery following Second Trimester Rupture of Membranes - Panzer, Alexis; Dotters-Katz, Sarah; Smid, Marcela; Boggess, Kim; Manuck, Tracy (American Journal of Perinatology, 2019)
Objective To identify factors associated with previable delivery in second trimester preterm rupture of membranes (PROM).Study Design We conducted a single-center retrospective cohort study of women with pregnancies complicated by second trimester PROM (14.0–21.9 weeks' gestation) from 2000 to 2015 who elected expectant pregnancy management and achieved at least 24 hours latency. Maternal characteristics and clinical factors were compared among pregnancies that reached viability (≥ 23.0 weeks) and pregnancies delivered before viability (< 23.0 weeks) using appropriate statistical methods.Results Of 73 pregnancies complicated by second trimester PROM, 49 (67%) delivered before viability. Maternal race, history of preterm birth, and tobacco use were similar between women who delivered < 23 weeks versus ≥ 23 weeks. Gestational age at PROM, cervical dilation > 1cm, Group B streptococcus carrier status, bacterial vaginosis, and chlamydial infection during pregnancy were similar between groups. Median time to delivery was significantly shorter in women who delivered < 23 weeks compared with those who reached ≥ 23 weeks (6 vs. 46 days, p < 0.01).Conclusion Previable delivery occurred in the majority of women with second trimester PROM. No maternal or clinical factors were associated with delivery prior to viability. Counseling women with second trimester PROM should include the inability to determine which pregnancies will reach viability.
Keywords: midtrimester; rupture of membranes; viability